2016
DOI: 10.5146/tjpath.2015.01345
|View full text |Cite
|
Sign up to set email alerts
|

Utility of direct immunofluorescence studies in subclassification of autoimmune sub-epidermal bullous diseases: a 2-year study in a tertiary care hospital

Abstract: Objective: sub-epidermal bullous disorders belong to immunobullous diseases which develop as a result of autoantibody action against epidermal basement membrane proteins. Clinically, they are tense bullae and do not rupture easily. They are classified into various forms based on histopathology and direct immunofluorescence patterns. This study was undertaken to assess the incidence of various sub-epidermal bullous disorders and the utility of direct immunofluorescence in accurately classifying them, and to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…6,7 There have been few case reports from India, but no study has characterized clinical and histopathological characteristics of Indian DH patients. [11][12][13] De et al reported 14 patients of DH from our center (data of these patients has been included in this study), and suggested DH may not be as uncommon in India as previously thought. 14 Two major reasons for apparent low prevalence of DH in Asians can be more consumption of rice and absence of HLA-DQ2 and DQ8.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…6,7 There have been few case reports from India, but no study has characterized clinical and histopathological characteristics of Indian DH patients. [11][12][13] De et al reported 14 patients of DH from our center (data of these patients has been included in this study), and suggested DH may not be as uncommon in India as previously thought. 14 Two major reasons for apparent low prevalence of DH in Asians can be more consumption of rice and absence of HLA-DQ2 and DQ8.…”
Section: Discussionmentioning
confidence: 66%
“…Dermatitis herpetiformis is a relatively rare disease with high prevalence in Scandinavian countries and in the USA . There have been few case reports from India, but no study has characterized clinical and histopathological characteristics of Indian DH patients . De et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 72% of the patients were in the pemphigoid group, which was consistent with the findings of international studies. 10 Although it is difficult to give a precise estimate of the disease incidence of other subepidermal autoimmune bullous dermatoses because of their rarity, an annual incidence rate ranging from 0.26 to 0.67 cases per million people per year has been reported for LAD, BLE, and EBA. 11 14 The incidence of DH ranges from 11.5 to 39.2 cases per 100,000 people.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 The correlation between BSLE and systemic involvements including lupus nephritis, neuropsychiatric SLE and hematologic abnormality have been documented. 62 DIF studies of BSLE are usually performed in the perilesional area with clinical non-lesional skin to demonstrate staining of IgG, IgM, C3 and IgA at the DEJ with linear or granular patterns 35,59,[62][63][64][65][66][67][68][69][70][71][72][73][74]. The positive yield from the DIF test was high, at approximately 85.7%-100%.…”
Section: Non-specific Lupus Cutaneous Manifestations Bullous Systemic...mentioning
confidence: 99%
“…The positive yield from the DIF test was high, at approximately 85.7%-100%. 35,59,[62][63][64][65][66][67][68][69][70][71][72][73][74] IgG was the most reported immunoreactant, while IgA was more common in BSLE than other forms of lupus. 65 Furthermore, IgA deposits were associated with disease activity.…”
Section: Non-specific Lupus Cutaneous Manifestations Bullous Systemic...mentioning
confidence: 99%